Students' Critical Reasoning Skills in Integrated Human Reproductive System Learning with Al-Quranic Values - Asna Nofiyanti; Endah Rita Sulistya Dewi; Muhammad Syaipul Hayat (Quagga: Jurnal Pendidikan dan Biologi, 2026)
Along with the development of the era, the emergence of the free sex phenomenon that can have an impact on the reproductive health of students. This proves a decline in character that is not in accordance with the profile of Pancasila students. To improve the profile of Pancasila students, a learning device that is integrated with the Qur'an in the material of the Human reproductive system was developed. In this study, to determine the effectiveness of the biology learning device integrated with the Qur'an in the material of the human reproductive system can improve the profile of Pancasila students, especially in the dimension of critical reasoning skills. The learning device was developed in a development research or Research and Development (R & D) using the ADDIE design, in grade IX students of MTs Al Furqon. The samples used in the study were two classes, namely the experimental class and the control class using purposive sampling techniques. To measure the level of critical reasoning skillss of students using pre-test and post-test questions. The data analysis technique used N-Gain to determine the effectiveness of the learning device. The results of the N-Gain percentage of the experimental class were 65.58%, while for the control class it was 44.03%. The integrated biology learning device of the Qur'an on the Human Reproductive System Material is stated to be quite effective in improving the profile of Pancasila students in the critical reasoning dimension.